The difficulty of the Linda conjunction problem can be attributed to its simultaneous concrete and unnatural representation, and not to conversational implicature. - Donovan, Sean; Epstein, Seymour (Journal of Experimental Social Psychology, 1997)
A study was conducted to examine whether the high occurrence of conjunction errors (CEs) to the notorious Linda conjunction problem can be explained by the violation of implicit conversational rules rather than by its concrete-unnatural representation, as suggested by cognitive-experiential self-theory. Subjects were provided with completely disclosing information. Although this method, aimed toward a rational mode of information processing, decreased CEs, a majority of subjects continued to make CEs. In addition, a graded series of problems intended to activate latent, intuitive knowledge, but not a procedure designed to supply supplementary information of a rational nature, decreased CEs. The implications of the results are considered in relation to two independent parallel modes of information processing—experiential-intuitive and rational-analytic—and it is concluded that the resistance of the Linda problem to a probabilistic solution is even greater than previously thought.